Effectiveness of an Interventional Program on Patient's Performance About Self-Care After Craniotomy Surgery - Hassan Jassim Hassan, Suad Jassim Mohammed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Craniotomy is a terrifying ordeal for patients and their families. The postoperative period is a patient's weakest and most vulnerable time. Despite teaching moments about postoperative directions, patients' concerns about daily living activities prior to and after discharge are the most common. Aim: To evaluate the effectiveness of an interventional program on patient's performance about self-care after craniotomy surgery. To find out the association between the effectiveness an interventional program on patient's performance about self-care after craniotomy surgery and demographic data of patients. Subjects and methods: A pre-experimental design (one group pre-test/ post-test design) is applied has been done to obtain the study goals. Forty-four patients had craniotomy surgery selecting by non-probability sample (convenience) sampling. Their age ranged from (20-60 and more) years old, fully conscious after operation. One group that gives interventional program. Using a valid and reliable questionnaire, data was collected. Results: the study shows there is a statistical significance deference between pre and post-test for study at p <0.05 which mean effectiveness of interventional programو this indicates to good improvement in total knowledge and practices of the patients about self-care performance after application of interventional program. Conclusion: At the post test, there was a high significant improvement in patients` knowledge and practices about self-care performance after application of the interventional program, this demonstrates the smoothness of the program that was designed for this purpose, as well as the ease with which it was accepted by all of the patients who took part. There is a statistical significant difference between demographics variables (age, gender, marital status, educational qualification and occupation) and effectiveness of interventional program among the two period (pre and post-test) for patient's knowledge and practices. Recommendation: Conducting specialized courses for medical and health staff concerned with the implementation of self-care programs after neurosurgery in neurosurgery wards.